Pengaruh Pelatihan dan Kepemimpinan terhadap Kinerja Pegawai Rumah Sakit Lanto Dg Pasewang Kab. Jeneponto Dengan Kepuasan Kerja Sebagai Variabel Intervening - Sriwati Sriwati; Moh. Akob Kadir; Syamsul Alam (Al-Buhuts, 2026)
Low employee performance at Lanto Dg. Pasewang Regional General Hospital in Jeneponto Regency is believed to be influenced by the quality of training and leadership, while the role of job satisfaction as a mediating variable linking the two has not yet been fully tested empirically at this regional hospital. This study aims to analyze the effects of training and leadership on employee performance and to test the role of job satisfaction in mediating this relationship. The study employed a quantitative survey design; the entire population of 227 employees was targeted using a saturation sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that training and leadership have a positive and significant effect on employee performance and job satisfaction at the hospital; job satisfaction also has a positive and significant effect on employee performance. Specifically, job satisfaction was found to mediate this relationship, with leadership exerting the most dominant influence on job satisfaction. These findings provide empirical evidence that improvements in employee performance are driven not only directly by training and leadership but also through increased job satisfaction a mechanism that has rarely been examined comprehensively at the Jeneponto District General Hospital.